Water Quality Pollution Index in Krueng Peusangan River Bireuen Regency - Hasriani, Cut; Ramli, Ichwana; Suhendrayatna, Suhendrayatna; Saiful, Saiful; Syaubari, Syaubari (Elkawnie, 2026)
Abstract: A continuous assessment of river water quality is a crucial aspect of water resources management and environmental protection. This research aims to assess the water quality status in Krueng Peusangan River that crosses Bireuen, Bener Meriah and Aceh Tengah Regency, Aceh Province, using the pollution index (IP) method. The water quality data used in this research is secondary data from monitoring results at several sampling locations from upstream to downstream over 10 (ten) years period from 2016 to 2025. Key parameters analyzed include physical, chemical, and biological parameters, such as pH, temperature, Dissolved Oxygen (DO), Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solids (TSS), nitrate, nitrite, phosphate, and bacteriological (Total Coliform). The pollution index calculation results show fluctuations in water quality status from year to year. In 2016-2018 and 2020-2021, the river was categorized as moderately polluted with IP values ranging from 5.829 to 8.898. Meanwhile, in 2019 and the 2022-2025 period, water quality experienced significant improvement and remained stable in the lightly polluted category, with IP values decreasing and remaining in the range of 1.243 to 3.378. This trend change needs to be observed by considering the change in the number of parameters for the IP calculation from 21 parameters (2016-2021) to 9 parameters (2022-2025). This indicates that the use of a more comprehensive parameter set (21 parameters) can provide higher analytical resolution and be sensitive to fluctuations in various pollutants. Therefore, parameter simplification has the potential to affect the interpretation of long-term pollution trends. Abstrak: Penilaian kualitas air sungai secara berkelanjutan merupakan aspek krusial dalam manajemen sumber daya air dan perlindungan lingkungan. Penelitian ini bertujuan untuk menentukan status kualitas air Sungai Krueng Peusangan yang melintasi Kabupaten Bireuen, Bener Meriah dan Aceh Tengah, Provinsi Aceh, dengan menggunakan metode Indeks Pencemaran (IP). Data kualitas air yang digunakan merupakan data sekunder hasil pemantauan pada beberapa titik sampling dari hulu hingga hilir selama periode 10 (sepuluh) tahun mulai tahun 2016 hingga 2025. Parameter kunci yang dianalisis meliputi parameter fisika, kimia, dan biologis, seperti pH, suhu, Dissolved Oxygen (DO), Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solids (TSS), nitrat, nitrit, fosfat, serta bakteriologis (Total Coliform). Hasil perhitungan Indeks Pencemaran menunjukkan fluktuasi status kualitas air dari tahun ke tahun. Pada tahun 2016, 2017, 2018, 2020, dan 2021, sungai berada dalam kategori tercemar sedang dengan nilai IP berkisar antara 5,829 hingga 8,898. Sementara itu, pada tahun 2019 dan periode 2022-2025, kualitas air mengalami perbaikan yang signifikan dan stabil masuk dalam kategori tercemar ringan, dengan nilai IP menurun dan bertahan di kisaran 1,243 hingga 3,378. Perubahan tren ini perlu dicermati dengan mempertimbangkan perubahan jumlah parameter untuk perhitungan IP dari 21 parameter (2016-2021) menjadi 9 parameter (2022-2025). Hal ini mengindikasikan bahwa penggunaan parameter yang lebih komprehensif, yaitu 21 parameter, dapat memberikan resolusi analitik yang lebih tinggi dan sensitif terhadap fluktuasi berbagai polutan, sehingga penyederhanaan parameter berpotensi memengaruhi interpretasi tren pencemaran jangka panjang.